2012
DOI: 10.1111/j.1445-5994.2011.02699.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risk stratification in severely anaemic Jehovah's Witness patients

Abstract: The aim of this retrospective cohort study was to identify early risk factors of mortality and develop a mortality risk stratification instrument for severely anaemic Jehovah's Witness patients. It has been shown that Jehovah's Witness patients with the Auckland Anaemia Mortality Risk Score (Auckland AMRS) of 0 to 3 had 4% mortality, Auckland AMRS 4 to 5 32%, Auckland AMRS 6 to 7 50% and Auckland AMRS 8 and above 83%. It is concluded that the Auckland AMRS predicts mortality of severely anaemic Jehovah's Witne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 10 publications
(15 reference statements)
0
18
0
Order By: Relevance
“…Previously, we have identified early mortality risk factors in severely anaemic JW patients, and proposed the Auckland AMRS. We have shown that the Auckland AMRS is associated with mortality of severely anaemic JW patients . With the development of the Hamilton AMRS, clinicians would be able to more closely monitor JW patients’ treatment progress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have identified early mortality risk factors in severely anaemic JW patients, and proposed the Auckland AMRS. We have shown that the Auckland AMRS is associated with mortality of severely anaemic JW patients . With the development of the Hamilton AMRS, clinicians would be able to more closely monitor JW patients’ treatment progress.…”
Section: Discussionmentioning
confidence: 99%
“…In the published literature, there are few cohort studies that consider causes of mortality of severely anaemic JW patients in isolation and are lacking in their predictive power . Recently, we proposed a mortality risk stratification approach for severely anaemic JW patients based on a calculation of the Auckland Anaemia Mortality Risk Score . However, this method does not consider anaemia‐related complications that occur during patients’ treatment and cannot be used for mortality risk adjustment and treatment monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Early involvement of Hospital Liaison Committees for JWs may help in facilitating communication between the patients and the health care community. The Hamilton Anaemia Mortality Risk Score could aid in clinical decision making …”
Section: Discussionmentioning
confidence: 99%
“…A composite score of these risk factors stratifies mortality rates of 4% to 83% (AMRS 0-3, 4% mortality; AMRS 4-5, 32% mortality; AMRS 6-7, 50% mortality; AMRS ≥ 8, 83% mortality). 7 The Hamilton AMRS further refined their risk model by including treatmentrelated mortality risk factors during hospitalization (shock, acute gastrointestinal bleeding, pneumonia, nadir Hb ≤ 7 g/dL, sepsis, worse congestive heart failure, neurologic complications [stroke and hypoxic encephalopathy]). Higher Hamilton AMRS scores were associated with high mortality (0-2, 4% mortality; 3-4, 29%; 5, 40%; ≥6, 67%).…”
Section: Definition Of Severe Anemia and Mortality Riskmentioning
confidence: 99%